Kota Bekasi: Suatu Analisis Pertumbuhan Ekonomi (2002-2012) - Abrar Abrar; Sri Martini; M. Hasmi Yanuardi (Jurnal Pendidikan Sejarah, 2023)
This research seeks to investigate Bekasi City's economic development from 2002 and 2012. The approach employed in this research is a descriptive analysis with an economic viewpoint. The main and secondary sources used were acquired, among other places, from the Bekasi City Government, the Bekasi City Statistics Center, the regional library in Bekasi City, and the national library. The heuristic and critical stages were utilized to gather the data needed for this investigation. The facts are then interpreted so that historical works can be presented. The results of the research show that Bekasi City's economy has evolved. Sectors like trade, industry, and agriculture all saw these changes. Because there is less and less land available for production, the development of the agricultural sector is showing signs of deterioration. 23,622 tons of paddy were produced in 2005. It decreased to 13862 tons in 2008. It decreased once again to 10,461 tons in 2012. The commercial sector is improving. Trade exports were worth $152513254 in 2005, while imports were worth $31698837. When compared to import value, which was $52493273, it then grew to $167814950 in 2008. It amounted to $983515065 in 2012, and the value of trade imports is $122847383. The City of Bekasi currently has a surplus because of the changes in the market. The largest surplus, $860,667,682, was recorded in 2012. Although the industry sector experienced a period of very constant growth from 2002 to 2010, with only an average of over two hundred industries, mostly in 2011–2012 did it frequently drop under two hundred industries. A surplus of value in trade is made possible by efficient transportation and population increase, especially in terms of labor Tujuan dari penelitian ini adalah menganalisis pertumbuhan ekonomi Kota Bekasi tahun 2002-2012. Pendekatan dalam penelitian ini menggunakan pendekatan ekonomi yang dituangkan dalam bentuk deskriptif analisis. Sumber yang digunakan berupa sumber primer dan sekunder yang didapatkan antara lain dari perpustakaan daerah Kota Bekasi, Badan Pusat Statistik Kota Bekasi, Pemda Kota Bekasi, dan perpustakaan nasional. Fakta-fakta yang disajikan dalam penelitian ini diperoleh melalui tahapan heuristik dan kritik. Kemudian fakta itu diinterpretasi agar dapat disajikan menjadi tulisan sejarah. Temuan penelitian menunjukkan telah terjadi perubahan ekonomi di Kota Bekasi. Perubahan tersebut terjadi pada sektor seperti pertanian, perdagangan dan industri. Sektor pertanian perkembangannya memperlihatkan kemunduran karena makin sedikitnya lahan produksi. Produksi padi pada tahun 2005 sebanyak 23622 ton. Pada tahun 2008 turun menjadi 13862 ton. Sampai tahun 2012 turun lagi menjadi 10461 ton. Sektor perdagangan yang memperlihatkan kemajuan. Pada tahun 2005 nilai ekspor perdagangan $152513254, sedangkan nilai impor perdagangan $31698837. Kemudian pada tahun 2008 meningkat menjadi $167814950, sementara nilai impor $52493273. Pada tahun 2012 telah mencapai $983515065 dan nilai impor perdagangan $122847383. Perkembangan yang terjadi dalam perdagangan itu memberikan hasil surplus untuk Kota Bekasi. Surplus terbesar tercapai pada tahun 2012 yang mencapai $860.667.682. Sementara sektor industri relatif stabil dari tahun 2002-2010 dimana jumlah industri rata-rata di atas 200 industri. Hanya tahun 2011-2012 yang cenderung turun menjadi dibawah 200 industri. Tercapainya nilai surplus dalam perdagangan itu didukung oleh transportasi yang memadai dan pertumbuhan penduduk terutama angkatan kerja.